Characteristics and management of the haemophilia‐associated pseudotumours. Issue 1 (19th November 2019) - Doyle, Andrew J.; Back, Diane L.; Austin, Steve
Abstract: The management of haemophilia‐associated pseudotumours presents an ongoing challenge to the haematologist, surgeon and interventional radiologist alike. There is a range of therapeutic approaches including factor replacement, embolization, radiotherapy and a variety of surgical interventions. However, there remains little evidence regarding the most appropriate treatment. We aimed to evaluate the available options of management for the haemophilia‐associated pseudotumour. A literature review was performed using relevant terminology and reviewed for treatment approaches and outcomes. The results demonstrated that most of the data is from single case reports with a small number of single‐ and multicentre case series. In total, 133 patients with 134 described pseudotumours were identified. Adequate haemostatic control with factor replacement was a key component to successful treatment. Surgical excision was the most commonly reported surgical intervention with various composites used for filling of the surgical cavity. The use of radiotherapy has been described particularly in the paediatric population and sites of difficult surgical access. Embolization can be considered as a method of presurgical optimization. Patients with both factor inhibitors and pseudotumours have poorer postoperative outcomes. This review demonstrates that although a lack of large‐centre, randomized studies, timely surgical intervention with adequate haemostatic support and the consideration adjuvant therapies in selected cases can achieve acceptable outcomes in this cohort of patients.